CAPITAL STRUCTURE AND PERFORMANCE OF MANUFACTURING COMPANIES ON BURSA MALAYSIA - Chen, Lee Fah; Asri, Marsidi (UNIMAS Publisher, 2023)
The study is carried out to examine the impact of capital structure on the performance of Malaysian manufacturing listed corporations. Specifically, the study attempts to investigate the relationship between short-term debt (STD), long-term debt (LTD), total assets (TA) and debt to equity (DE) on the return on equity (ROE) of manufacturing companies listed on Bursa Malaysia. To achieve this objective, the data is collected from the annual data of 30 Malaysian manufacturing companies listed on Bursa Malaysia from 2010 to 2017. The annual reports of the selected companies are available on the Bursa Malaysia webpage. In this study, the data is analyzed using Eviews 9 software. The findings of the study show that total assets (TA) and debt to equity (DE) have negative significant effect on the return on equity (ROE) whereas short-term debt (STD) and long-term debt (LTD) have positive significant relationship with firm financial performance. The study thus contributes towards better understanding on the relationship between the capital structure and performance of the manufacturing companies in Malaysia.